A preliminary study of copy number variation in Tibetans. - Yong-Biao Zhang (Public Library of Science (PLoS), 2012)
Genetic features of Tibetans have been broadly investigated, but the properties of copy number variation (CNV) have not been well examined. To get a preliminary view of CNV in Tibetans, we scanned 29 Tibetan genomes with the Illumina Human-1 M high-resolution genotyping microarray and identified 139 putative copy number variable regions (CNVRs), consisting of 70 deletions, 61 duplications, and 8 multi-allelic loci. Thirty-four of the 139 CNVRs showed differential allele frequencies versus other East-Asian populations, with P values <0.0001. These results indicated a distinct pattern of CNVR allele frequency distribution in Tibetans. The Tibetan CNVRs are enriched for genes in the disease class of human reproduction (such as genes from the DAZ, BPY2, CDY, and HLA-DQ and -DR gene clusters) and biological process categories of "response to DNA damage stimulus" and "DNA repair" (such as RAD51, RAD52, and MRE11A). These genes are related to the adaptive traits of high infant birth weight and darker skin tone of Tibetans, and may be attributed to recent local adaptation. Our results provide a different view of genetic diversity in Tibetans and new insights into their high-altitude adaptation.